Theorizing Race and Gender in the Anthropocene. Issue 4 (1st October 2020) - Reyes, G. Mitchell; Chirindo, Kundai
Abstract: What does it mean to think about race and gender in the Anthropocene? In collaboration with Achille Mbembé's recent work, this article argues that the Anthropocene requires rethinking race and gender and that retheorizing race and gender might just offer avenues for mitigation and adaptation of/to radical ecological and cultural transformation. To understand how we arrived at the Anthropocene and how race and gender are implicated, the article first traces the emergence and articulation of race and gender alongside the discursive formations of colonialism, capitalism, and necropolitics. These relations, effected in the establishment of differential temporalities, catalyzed our arrival at the Anthropocene. The Anthropocene, we argue, marks the generalization of precarity that was once concentrated among those disempowered through perceived racial and gender differences. Turning to Mbembé's radical humanism as antidote, we conclude the article with some rhetorical and ethical principles for (re)asserting the plurality of ontology, part of which is positioning rhetoric as a counterforce to the asymmetrical distributions of precarity. Rhetoric as an analytic for tracing necropolitics, rhetoric as an inventional resource for the rearticulation of racialized and gendered subjectivity, and rhetoric as a counterhegemonic challenge to necropolitical representation—these we argue are central to the future of the field in the age of the Anthropocene.